Corporate governance and effect in fintech: Evidence from Gulf Cooperation Council banking sector - Aws AlHares (17541741) (2023)
This study looks at the banking sector in the Gulf Cooperation Council (GCC) from 2013 to 2021 to determine the impact that corporate governance had on financial innovation, as well as the impact that financial innovation had on performance. Thirty (30) commercial banks with 270 annual observations were selected, including 5 banks from each country. In order to quantify the factors at play, we queried databases such as Refinitiv Eikon and Fitch Connect. The research indicates that banks with a greater number of directors with backgrounds in finance or accounting, a higher attendance rate of directors, a higher ratio of independent directors, a higher average director education level, and a greater number of directors with a background in finance or accounting, provide more cutting-edge financial services. Since 2017, corporate governance has been a more significant factor in how banks approach providing new, cutting-edge financial services to their customers. Furthermore, a bank’s profitability and value will rise in direct proportion to the extent to which it provides cutting-edge financial services. Furthermore, the value of financial holding subsidiary banks could rise if they provided more innovative financial services. However, the same action taken by non-financial holding banks could have a negative impact on their profitability. Other Information Published in: Corporate and Business Strategy Review License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.22495/cbsrv4i1art9